The Role of The State in Protecting Personal Data under Law Number 27 of 2022 - Cornelia Ayu Hafsari; Labib Muttaqin (Proceeding International Conference Restructuring and Transforming Law, 2023)
The purpose of this research is to find out the role of the state and to find out the juridical review of legal protection in guaranteeing the security of personal data in terms of Law Number 27 of 2022 concerning Protection of Personal Data which in its analysis uses a conceptual approach and a legal approach. invitation (law approach). The results of this study are that the PDP Law provides protection for a person's personal data and provides strict sanctions for perpetrators of cybercrime, including phishing perpetrators. The government has an important role in implementing the PDP Law, among others by imposing sanctions on cybercrime perpetrators, strengthening cooperation between government agencies in the field of cybersecurity, and providing a sense of security and comfort for the public in conducting online transactions and maintaining personal security. data. The Personal Data Protection Authority was established by the government to formulate policies and oversee personal data protection as well as provide administrative sanctions and assist law enforcement in dealing with personal data crimes. The PDP Law and related government actions are expected to minimize phishing practices and protect Indonesian people's personal data.